Research on Determination of the Bulgarian Industrial Enterprises’ Competitiveness - Shterev, Nikolai (Research Papers, 2012)
Certainly, the issues of the competitiveness of the economy and its individual economic entities are matters of very great importance for Bulgaria. Therefore, the management of competitiveness is focused on continuously improving indices that evaluating this competitiveness.Although the global theory and practice have both developed and implemented a variety of methodological schemes, criteria and indicators for evaluating the competitiveness, there is still not unambiguously answer of the next question: When competitiveness indicators are improving – does that mean a real and increased competitiveness of the economy and its enterprises?The study seeks to answer the question above. The firm and product level are set as priority issues at this research. Moreover, by analyzing of application data, the study seeks an explanation why some companies are more competitive than others and why a company "lost" its competitiveadvantage over time.